A Retrospective Study on Equine Herpesvirus‐1 Associated Myeloencephalopathy in France (2008–2011). (September 2014) - van Galen, G.; Leblond, A.; Tritz, P.; Martinelle, L.; Pronost, S.; Saegerman, C.
Abstract : Reasons for performing study: Diagnosis of equine herpesvirus‐1 associated myeloencephalopathy (EHM) can be troublesome, but early recognition and knowledge of risk factors are primordial for prevention and control. Objectives: 1) Improvement of early clinical recognition, and 2) identification of factors potentially of importance for spread. Study design: Retrospective descriptive study of EHM cases and statistical comparison to acutely neurologically affected horses negative for EHM. Methods: Files from a French epidemiosurveillance programme for equine infectious neurological diseases (2008–2011) were reviewed. Cases were considered EHM (n = 26) based on presence of acute neurological signs and laboratory confirmation. Cases were considered control cases (n = 29) when reported to be suffering from acute neurological diseases, but negative for EHM. A subgroup of controls was created that excluded cases with peripheral neuromuscular diseases (n = 21). Univariate and multivariate analysis and classification and regression tree analysis between groups were performed to identify diagnostic markers and risk factors. Results: EHM had a fatality rate of 46% and occurred often in isolated cases. They frequently showed ataxia, paresis and cauda equina affection, but the clinical picture was variable. Univariate analysis identified the following variables as more associated to EHM than to control groups: new horse introduced in herd, vaccination, cauda equina affection, larger herd size, and saddle horses. In the multivariate analysis, new horse introduced in herd and cauda equina affection could be retained. CART analyses identified herd size, month of occurrence, new horse introduced in herd and cauda equina affection as main predictors for EHM. Conclusions: Isolated EHM cases occur frequently, accentuating the diagnostic difficulty. History and clinical examination of acutely neurologically affected horses can potentially improve early recognition of EHM. Risk factors were in accordance with other studies, although in a different geographic location and study setup, and therefore strengthen their importance for spread of EHM. Acknowledgements: Christel Marcillaud‐Pitel and Charlène Daix are gratefully acknowledged for their help with data collection. Ethical animal research: Ethical committee oversight not currently required by this congress: retrospective study of clinical records. Explicit owner informed consent for participation in this study was not stated.Sources of funding: RESPE.Competing interests: None.